Coronary Artery Bypass Graft Type and Outcomes in Maintenance Dialysis - Shilane, D. (2013)
AIM: Patients with end-stage renal disease (ESRD) on maintenance dialysis have a high burden of coronary disease. Prior studies in non-dialysis patients show better outcomes in coronary artery bypass surgery using the internal mammary artery (IMA) compared with the saphenous vein graft (SVG), but less is known about outcomes in ESRD. We sought to compare the effectiveness of multivessel bypass grafting using IMA versus SVG in patients on maintenance dialysis in the United States. METHODS: Cohort study using data from the United States Renal Data System to examine IMA versus SVG in patients on maintenance dialysis undergoing multivessel coronary revascularization. We used Cox proportional hazards regression with multivariable adjustment in the full cohort and in a propensity-score matched cohort. The primary outcome was death from any cause; the secondary outcome was a composite of non-fatal myocardial infarction or death. RESULTS: Overall survival rates were low in this patient population (5-year survival in the matched cohort 25.3%). Use of the IMA compared to SVG was associated with lower risk of death (adjusted hazard ratio [HR] 0.88, 95% confidence interval [CI] 0.84-0.92) and lower risk of the composite outcome (adjusted HR 0.89; CI 0.85-0.93). Results did not materially change in analyses using the propensity-score matched cohort. We found similar results irrespective of patient sex, age, race, or the presence of diabetes, peripheral vascular disease or heart failure. CONCLUSION: Although overall survival rates were low, IMA was associated with lower risk of mortality and cardiovascular morbidity compared to SVG in patients on dialysis.